Importance of Oil Plants in Nutrition (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article focuses on the main oilseed crops, their role in human health and disease, and highlights new developments that may provide even greater benefits in the future. Oilseed crops are cultivated primarily for the oil contained in their seeds. Oilseed crops are rich in protein and also have high oil content. Therefore, they are not only a good source of protein but also a concentrated source of energy. Oilseed proteins can be used as food in the form of whole seeds or in the form of oil-extracted meals. Oilseeds and their derivatives, vegetable oils and meals, are in high demand worldwide, and it is necessary to identify and assess the main challenges in their production. This will help to develop and support actions by various stakeholders to ensure a sustainable future for these crops.